THE IMPACT OF CONSUMER ATTITUDES ON ONLINE SHOPPING, INCLUDING SOCIAL MOTIVATIONS, ESCAPISM MOTIVATIONS, AND VALUE MOTIVATIONS, IN RELATION TO ONLINE PURCHASE INTENTIONS - Cen Lu; Chandra Kuswoyo; Reicheana Koesala Zirho (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The development of technology and the internet has changed people's shopping behavior, especially the millennial generation. This study aims to analyze the attitude on online shopping of the millennial generation and compare it with the population as a whole. This study also provides an explanation of the online shopping behavior of consumers in the millennial generation group, as well as being the basis for developing teaching materials in customer insight and consumer behavior courses. The Millennial generation is a group of individuals who have different awareness of the impact of historical events they experience. They tend to be more tech-savvy and spend less money on purchases. The study highlights the need to understand the Millennial generation further because they are not monolithic. Understanding generational differences and their impact on online shopping is important for effective target audience segmentation. Meanwhile, purchasing behavior describes whether consumers actually buy the products they want, with purchase intention as a proxy variable to measure purchasing behavior. This study is a type of quantitative research that uses a survey method to collect data from the West Java millennial generation who are involved in online purchase intention. The population is the West Java millennial generation, and the sample was taken using a purposive sampling technique. Testing of the research instrument was carried out with validity using the Pearson Correlation test and reliability with Cronbach's alpha. The data was processed using Moderate Regression Analysis (MRA) with SPSS version 25. The results of the study showed that attitudes on online shopping and value motives influence online shopping intention. Social motives and escapism motives do not affect online shopping intention.